Pelatihan Pembukuan Sederhana pada Warung Bakso dan Warung Miayam di Kelurahan Canden Jetis Bantul - Monika Weni Cahyasari; Nugraeni Nugraeni (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Financial recording is very important and has many benefits for measuring performance in various business activities. Lack of knowledge in managing financial records is one of the obstacles in managing MSMEs at the sub-district level. The aim of this community service is to provide outreach regarding the importance of financial recording and provide training regarding simple financial bookkeeping. The method used during this service activity is observation and interviews, outreach and training, then evaluation and mentoring. The result of this service activity is that partners can understand the benefits and process of financial recording for the continuity of their business.